2009
DOI: 10.1186/1423-0127-16-23
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functional defect of three novel Brugada syndrome related cardiac sodium channel mutations

Abstract: The Brugada syndrome is characterized by ST segment elevation in the right precodial leads V1-V3 on surface ECG accompanied by episodes of ventricular fibrillation causing syncope or even sudden death. The molecular and cellular mechanisms that lead to Brugada syndrome are not yet completely understood. However, SCN5A is the most well known responsible gene that causes Brugada syndrome. Until now, more than a hundred mutations in SCN5A responsible for Brugada syndrome have been described. Functional studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…Those results were basically consistent with previous studies (16,17). As for R965C-R1309H mutations, compared to R1309H mutation, it induced more significant depolarization shift of activation curve, V 1/2 and slope factor, suggesting that Na v 1.5 R965C-R1309H channel was activated at the much more depolarized membrane potential and displayed slower activation (Supplement 3).…”
Section: Electrophysiological Characteristicssupporting
confidence: 92%
See 3 more Smart Citations
“…Those results were basically consistent with previous studies (16,17). As for R965C-R1309H mutations, compared to R1309H mutation, it induced more significant depolarization shift of activation curve, V 1/2 and slope factor, suggesting that Na v 1.5 R965C-R1309H channel was activated at the much more depolarized membrane potential and displayed slower activation (Supplement 3).…”
Section: Electrophysiological Characteristicssupporting
confidence: 92%
“…Consistent with previous literatures reported (16,17), as shown in the Figure 4A-C and Table 2, the R1309H mutation, but not R965C mutation, significantly reduced the Na + current density at a series of test potentials ranging from -45 mV to -15 mV when compared to the WT group (Supplement 1). More importantly, we found that R965C-R1309H mutations resulted in a more severe reduction in Na + current density ranging from -45 mV to 30 mV compared to the WT group.…”
Section: Electrophysiological Characteristicssupporting
confidence: 91%
See 2 more Smart Citations
“…Functional studies of many different mutations in the gene have been performed and they all lead to a reduction in net sodium current due to one or more of following reasons (Antzelevitch et al, 2005); (1) reduced current density due to failure of the sodium channel to express or defect trafficking of the channel (Baroudi et al, 2001; Valdivia et al, 2004; Pfahnl et al, 2007), (2) a shift in the voltage- and time-dependence of sodium channel current activation, inactivation or reactivation (Keller et al, 2005; Hsueh et al, 2009; Calloe et al, 2013), or (3) entry of the sodium channel into an intermediate state of inactivation from which it recovers relatively slower than normal (Bezzina et al, 1999; Veldkamp et al, 2000; Chiang et al, 2009). A number of knock-out mouse models support the central role of SCN5A in the pathogenesis of BrS (Killeen et al, 2008; Derangeon et al, 2012).…”
Section: Genetic Basis Of Brsmentioning
confidence: 99%